Genetic structure and differentiation at a short-time scale of the introduced calcarean sponge Paraleucilla magna to the western Mediterranean. In: Maldonado M, Turon X, Becerro MA, Uriz MJ (eds) Ancient Animals, New Challenges. Sponge Research Developments. - Guardiola, M.; Frotscher, J.; Uriz, M.-J. (Hydrobiologia, 2012)
The allochthonous calcarean sponge Paraleucilla magna has proliferated in the western Mediterranean during the last decade, where it currently shows a highly patchy distribution with dense populations in the neighboring of sea farms and slightly eutrophised marinas, and more sparse populations in well-preserved habitats. To gain knowledge about the species invasive capacity, we studied spatial genetic differentiation and structure, clonality, and temporal differentiation, in three close populations of P. magna at the NE of the Iberian Peninsula, in three successive years. The study hypothesis was that the species is able to proliferate under favorable conditions in newly colonized habitats but populations can easily disappear where perturbations occur with some frequency. Samples were genotyped for nine polymorphic microsatellites. Spatial genetic structure was found in the three populations of 2006. One population disappeared in 2007, and the other two remained slightly differentiated, while the three populations were in place again in 2008, and showed very low (but significant) FST values, and non-significant D values. Low but statistically significant differentiation also occurred for the three populations between years. Results showed high-allele diversity, but heterozygote deficit and changes in allele frequencies in the populations over the 3 years, which are consistent with some genetic drift. The whole population descriptors pointed to the species as a good opportunistic colonizer as it has been hypothesized, but highly sensitive to stochastic events affecting recruitment. This suggests a high impact of the species in favorable habitats (sea culture and sheltered zones) and a low-medium influence in native communities.
Proceedings of the 8th International Sponge Conference